Analysis of Al-Qur'an Verses Used in Ruqyah Syar'iyyah Practice as Treatment Method : A Thematic Interpretation - Nurhikam, Nurhikam; Mumtaz, Auziah; Fajrussalam, Hisny (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
Establishing from the increasingly major phenomenon of ruqyah therapeutic development. The research described here tries to gain an understanding of  Holy Quranic verses in the practice of ruqyah syar'iyyah, as well as how these verses connect to current medical and psychological concepts. Researchers used a thematic interpretation (maudhu'i) approach and library research techniques to analyze the findings in order to get some insight to this issue at hand. This approach was chosen to comprehend the context and significance of Quranic verses used for the practice of ruqyah syar'iyyah. The Holy Quran, Hadith, books, manuscripts, writings, and works from multiple genres of literature that are related to the issue at hand were used as research data sources. The findings of this research indicate that there's a significant connection between each verse of the Al-Qur'an and the medical approach of ruqyah syar'iyyah. It is expected the following research conducted will help the scholars who have an interest in this issue face a more thorough understanding of how the verses of the Quran are applied in the practice of ruqyah syar'iyyah.